MATHEMATICAL MODELLING IN PEDAGOGY - Krasniuk, S.O. (SWorld-Ger Conference proceedings, 2024)
The main advantage of mathematical modeling in education is the ability to objectively analyze complex systems that include the interaction of students, teachers, educational institutions and external factors. The use of mathematical modeling allows not o